Unusual variants of mycosis fungoides - Virmani, Pooja (Diagn Histopathol (Oxf), 2016)
Conventional presentations of mycosis fungoides may be diagnostically challenging, particularly in light of the controversial boundaries defining the disease. Variant presentations of this cutaneous T-cell lymphoma add a further layer of complexity, requiring a sophisticated and informed perspective when evaluating lymphoid infiltrates in the skin. Herein we discuss well-defined (WHO-EORTC) variants pagetoid reticulosis, granulomatous slack skin and folliculotropic mycosis fungoides as well as less well-defined morphologic/architectural variants, and divergent immunohistochemical presentations of this typically indolent T-cell lymphoproliferative disease.